Penerapan Model Pembelajaran Circuit Learning Berbantuan Media Microsoft Power Point untuk Meningkatkan Hasil Belajar IPS pada Peserta Didik Kelas IV SDN 3 Palangka Tahun Pelajaran 2016/2017 - Siti Paramida; Ade Salahuddin Permadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
This study aims to: (1) To describe the learning activities of fourth grade students during Social Studies learning by applying the Circuit Learning learning model assisted by Microsoft PowerPoint media and (2) To improve the learning outcomes of fourth grade students during IPS learning by applying the model learning Circuit Learning supported by Microsoft PowerPoint media. The type of research used in this study was Classroom Action Research (PTK) with research subjects all of the fourth-grade students of Palangka Elementary School-3 which numbered 35 students. Data collection techniques in this study used observation and tests. Data analysis using qualitative, quantitative data analysis. The results of this study indicate that: (1) Activity of Grade IV students in Palangka Elementary School-3 of 2016/2017 Academic Year in Social Studies learning after applying the Circuit Learning model assisted by Microsoft PowerPoint media to be very good because students are active and enthusiastic in following the process learning. The observations of teacher activities on teaching and learning activities carried out by observer I and Observer II during the social studies learning the process in the first cycle were 3.73 in the outstanding category, and the universal aspect of the students was 3.57 in the very well typed. (2) There is an increase in social studies learning outcomes by implementing Microsoft PowerPoint Circuit Assisted learning model on social studies subjects in grade IV of the 2016/2017 SDN-3 Academic Year. This is indicated by the learning outcomes seen through the class average in cycle I which is equal to 80 and the completeness percentage of students in classics namely 100%, from the predetermined provisions namely for KKM of 65 and completeness criteria in classical 85% with this then It can be concluded that there is an increase in social studies learning outcomes after applying the Learning Learning model assisted by Microsoft PowerPoint